The Relationship between Conversion Factors and Health: Evidence from the Ready-Made Garment Workers in Bangladesh - Nasrin, Shamima; Rasiah, Rajah; Baskaran, Angathevar; Khan, Hafiz T.A. (SAGE Publications, 2019)
This study examined the association between health condition and conversion factors (i.e. environmental, individual and social) among workers in the ready-made garment (RMG) industry in Bangladesh. It used data gathered from a cross-sectional survey of 775 RMG workers in the Dhaka and Narayanganj districts. Using multiple logistic regression, the study found that: (1) achieving good health among RMG workers is hindered by various factors including high job-related demands, high noise levels, workplace crowding, heavy workloads, and low level of educational attainment; (2) job-related rewards and marital status have contributed to achieving good health; (3) health condition of workers is worse for women than for men; and (4) poor health condition is more prevalent among the oldest age group than in the lowest age category. The main contributions of this research: (1) this study develops a comprehensive framework to determine the factors affecting the health condition of manufacturing workers in general, and RMG workers in particular; and (2) it also examines the effects of both psychosocial and physical working conditions on the health of RMG workers.